Sustainable Food Systems – Focus on Organic Farming of Fresh Fruits and Vegetables - Gabriel POPESCU; Marian Catalin CUCU; Ioana PANAIT (Communications of International Proceedings, 2021)
The paper is a theoretical study that focuses on the contribution of producers and consumers in its actions aimed at the sustainability of agriculture and is based on the presentation of the main characteristics of fruits and vegetables market in Romania and the particularities of the organic farming in Romania, both as integrated parts of the sustainable development of food systems. The paper includes a quantitative research based on statistical data for the two categories studied to identify the size of the Romanian market and a comparison at the level of the European Union. Based on the studied data, an analysis was performed regarding the development potential of the fruits and vegetables market and organic farming in Romania, in accordance with the principles of sustainability
Keywords: Agri-Food Supply Chain; Sustainable Development; Trends; Sustainable Food System